Numerical simulation of profiled steel sheeting in compression: a case of double-deck paneling / Nurul Huda Suliman - Suliman, Nurul Huda (Universiti Teknologi MARA Cawangan Pahang, 2008)
Profile Steel Sheet Dry Board (PSSDB) composite material is one of the innovations in construction technology for a variety of structural purposes such as floor and roof unit. This paper aims to simulate the behavior and potential of cellular arrangement of two PSSDB as a panel unit under compression loading. A mathematical and computational model is presented for the analysis to predict the potential of the PSSDB. A programme based on a finite element analysis is developed using LUSAS 13.5 to determine the buckling and maximum load that can be supported by PSSDB. The same material property through thickness is used to model single and cellular arrangement of two PSSDB. These models are analysed and the results obtained are also compared to prove that the cellular arrangement of two PSSDB could offer a better strength than single PSSDB. The displacement, buckling and ultimate load have shown that the cellular arrangement of two PSSDB can be used as a panel in the construction industry.